An innovative approach of bioremediation in enzymatic degradation of xenobiotics. Issue 1 (2nd January 2022) - Rathore, Shruti; Varshney, Ayushi; Mohan, Sumedha; Dahiya, Praveen
ABSTRACT: Worldwide, environmental pollution due to a complex mixture of xenobiotics has become a serious concern. Several xenobiotic compounds cause environmental contamination due to their severe toxicity, prolonged exposure, and limited biodegradability. From the past few decades, microbial-assisted degradation (bioremediation) of xenobiotic pollutants has evolved as the most effective, eco-friendly, and valuable approach. Microorganisms have unique metabolism, the capability of genetic modification, diversity of enzymes, and various degradation pathways necessary for the bioremediation process. Microbial xenobiotic degradation is effective but a slow process that limits its application in bioremediation. However, the study of microbial enzymes for bioremediation is gaining global importance. Microbial enzymes have a huge ability to transform contaminants into non-toxic forms and thereby reduce environmental pollution. Recently, various advanced techniques, including metagenomics, proteomics, transcriptomics, metabolomics are effectively utilized for the characterization, metabolic machinery, new proteins, metabolic genes of microorganisms involved in the degradation process. These advanced molecular techniques provide a thorough understanding of the structural and functional aspects of complex microorganisms. This review gives a brief note on xenobiotics and their impact on the environment. Particular attention will be devoted to the class of pollutants and the enzymes such as cytochrome P450, dehydrogenase, laccase, hydrolase, protease, lipase, etc. capable of converting these pollutants into innocuous products. This review attempts to deliver knowledge on the role of various enzymes in the biodegradation of xenobiotic pollutants, along with the use of advanced technologies like recombinant DNA technology and Omics approaches to make the process more robust and effective.